"Macron demission!": Loss of significance generates violent extremism for the Yellow Vests through feelings of anomia. (January 2021) - Mahfud, Yara; Adam-Troian, Jaïs
After over 2 months of demonstration, 12 casualties, 3, 142 people injured, and more than 5, 000 people in custody, the question of why the Yellow Vest (YV) protests turned so violent remains. In line with a significance quest perspective on violent extremism (Kruglanski & Orehek, 2011), the present contribution assessed whether the motivation to restore a sense of control and purpose could explain why French citizens engage in violent YV extremism. We hypothesized that personal loss of significance should predict intentions to display YV violence through increased feelings of anomia. Cross-sectional (Study 1, N = 776, general population) and experimental (Study 2, N = 511, undergraduate students) mediation analyses corroborated this hypothesis, in addition to other known predictors of violent extremism. These results provide a first existential-motivational explanation of YV violence in France and highlight the key role of anomia as a predictor of violent extremism under loss of significance.